A Production of operations management study on Corro-Coat, Inc. - De Leon, Salve Regina (College of Engineering, 2003)
Corro-Coat, Inc. is an ISO certified company, producing powder coatings. The company has a 70% market share, placing them on top of its industry. Their major customers are Concepcion-Carrier Industries, Daikin, National and Feathers, which are all air conditioner manufacturers. Aside from these, they also produce powder coatings for architectural, appliances and furniture purposes.The raw materials used by the company are all imported from Europe and other countries in Asia. The Operations Management techniques of the company were documented and analyzed in this study. The demand management, capacity planning, supply chain management and aggregate planning of the company were focused on. After documenting, three major problems were considered for in-depth analysis. These problems are: (1) High deviation between forecasted and actual demand, (2) Low Machine utilization with respect to effective capacity and (3) Raw Material Shortages. For the above problems, the proponents came up with some recommendations. For the first problem, the use of Multiplicative Seasonal model is suggested to be used as the company's forecasting technique in order to make the efficiency of the machines higher. Lastly, use of MRP software is recommended in order to minimize the occurrences of shortages. For the recommendations for problems 1 and 2, the proponents would provide a worksheet in order to serve as guideline for the upgrading of the company's record system. Also, some areas were considered by the group for further study. The implementation of JIT system in their production, excluding the raw materials inventory, is suggested since their production depends on job orders from customers. Also, using JIT, the efficiency of the machines as well as the workers would be further increased. Using a software for the scheduling of production is also considered by the group applicable to the company.